(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: The aim of the present study was to do an overview of the arch dimension for various populations. Also, to evaluate the various type of measurement methods and sexual disparities. Two reviewers independently performed the selection process and the quality of studies was assessed. Method: Studies published form January 2000 until October 2015 were identified in electronic databases: Pubmed, Scopus, Science direct, Web of Science, Medpilot and Medline using keywords.Criteria used included: observational studies, Arch size measured, Permanent dentition, Arch dimension investigated via plaster and digital dental models, measurement via calipers and computers software’s. Result: The forest plots showed the continuous trend for the greater arch dimension for male in relation to female. The current overview showed the arch dimension and its disparities for various populations. Conclusion: The various methods to assess arch dimension should be carefully considered and well conducted as part of the clinical assessment of orthodontic treatment, since arch dimension could influence the diagnosis and treatment planning of orthodontist. Bangladesh Journal of Medical Science Vol.18(1) 2019 p.30-35